First-principle studies of gallium oxide-oxygen vacancy ( β -Ga 2 O 3 ) - Здоровец , М. В.; Усеинов , A. Б.; Акилбеков , A. Т.; Popov , A. I.; Койшыбаева , Ж. К.; Платоненко , А. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Gallium oxide β -Ga 2 O 3 is a promising material in optoelectronics and radiation detection. Despite the wide range of studies carried out, an important problem is the influence and role of intrinsic defects on the electronic properties of a crystal. In this article, we present calculations of the formation energy and the levels of transitions of the charge state of oxygen vacancies in a β -Ga 2 O 3 crystal using the B3LYP hybrid exchange- сorrelation functional and the approximation of linear combinations of atomic orbitals. As a result, the formation of an oxygen vacancy in β -Ga 2 O 3 leads to the presence of deep donor levels, as a result of which it was assumed that the formation of oxygen vacancies does not play a significant role in the n-type conductivity in β -Ga 2 O 3 crystals.